Islam Sebagai Way Of Life Sebagai Fondasi Pemikiran Ekonomi Islam dalam Konteks Ekonomi Global - Taufik Hadi Permana; Sarmiana Batubara (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Islam is not merely regarded as a ritual doctrine, but also as a way of life that guides all aspects of human existence, including economic activities. Islamic economic thought is derived from normative values such as justice, balance, and social responsibility, which are grounded in the maqāṣid al-sharī‘ah. In the current global economic landscape, dominant economic systems exhibit various structural weaknesses, including income inequality, recurring financial crises, and environmental degradation. These conditions create a growing need for an alternative economic paradigm that not only focuses on growth but also emphasizes welfare and social justice. This study aims to examine Islam as a way of life that serves as a philosophical foundation in the development of Islamic economic thought to address contemporary global economic challenges. The research employs a descriptive qualitative method with a literature review approach, analyzing relevant classical and contemporary sources. The findings indicate that Islamic economic thought has a strong connection to addressing modern economic problems, particularly through the integration of ethical values, distributive justice, and the principle of sustainability. Islam as a way of life acts not only as a critique of conventional economic systems but also as a conceptual framework that can enrich global economic discourse with a more humane and collectively oriented approach. Islam tidak sekadar dianggap sebagai ajaran ritual, melainkan juga sebagai gaya hidup yang memandu semua aspek kehidupan manusia, termasuk dalam ekonomi. Pemikiran ekonomi Islam berasal dari nilai-nilai normatif seperti keadilan, keseimbangan, dan tanggung jawab sosial yang berlandaskan pada maqāṣid al-syarī‘ah. Dalam situasi ekonomi global saat ini, sistem ekonomi yang dominan menunjukkan berbagai kelemahan struktural, seperti ketidakmerataan pendapatan, krisis finansial yang terjadi berulang kali, serta kerusakan lingkungan. Kondisi ini menciptakan kebutuhan akan paradigma ekonomi alternatif yang tidak hanya fokus pada pertumbuhan, tetapi juga pada kesejahteraan dan keadilan sosial. Penelitian ini bertujuan untuk mengkaji Islam sebagai gaya hidup yang menjadi dasar filosofis dalam pengembangan pemikiran ekonomi Islam untuk menjawab tantangan ekonomi global saat ini. Metode penelitian yang dipakai adalah kualitatif deskriptif dengan pendekatan pengkajian literatur, melalui analisis terhadap sumber klasik dan kontemporer yang relevan. Temuan penelitian menunjukkan bahwa pemikiran ekonomi Islam memiliki keterkaitan yang kuat dalam menghadapi permasalahan ekonomi modern, terutama melalui integrasi nilai-nilai etika, keadilan distribusi, dan prinsip keberlanjutan. Islam sebagai gaya hidup tidak hanya bertindak sebagai kritik terhadap ekonomi konvensional, tetapi juga sebagai kerangka konseptual yang dapat memperkaya diskursus ekonomi global dengan pendekatan yang lebih manusiawi dan berorientasi pada kepentingan bersama.